Optimum formulation design of natural fiber-reinforced composites (NFRC) for automotive applications. (April 2022) - Zerin, Nagma; Quinlan, Patrick; Simon, Leonardo
Natural fiber-reinforced composites (NFRC) are cheaper and more eco-friendly alternatives compared to synthetic composites for automotive applications. As there is limited understanding about the balance of different physical properties in NFRC, optimizing these properties is an important consideration for a more widespread application of NFRC. The goal of this research was to statistically develop an optimum formulation for oat-hull-reinforced polypropylene composite. Mechanical properties of the composites were first experimentally measured. Then, the mixture design experiment approach was utilized to generate response models for different properties, and diagnostic tools were utilized to validate the models. In addition to optimizing the desired material properties, the overall cost of the composite was minimized, which adds novelty to the work.